PENGARUH KEBIJAKAN DIVIDEN, STRUKTUR MODAL, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Sub Sektor Otomotif yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Ferro Trisya Putra Pratama; Prita Anugrah Widowati (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
This research aims to examine the effect of dividend policy, capital structure and profitability on firm value (PBV). While, research was quantitative. Moreover, the population was automotive companies, which were listed on Indonesia Stock Exchange (IDX) during 2019-2022. Furthermore, the data collection technique used purposive sampling, in which the sample was based on criteria given. In line with there were 9 automotive companies as the sample. In total, there 36 data from 4 years of observasion. Additionally, the data were secondary which in the form of financial annual report. In addition, the data analysis technique used multiple linier regression with SPSS tools. Based on the results of data anlysis using the t test, it is known that dividend policy (DPR) has a negative effect on firm value, Capital structure (DER) has a negative effect on firm value, and profitability with (ROA) has a positive effect on firm value. Meanwhile, based on the results of data analysis using the F test, it is known that simultaneously dividend policy, capital structure and profitability have a significant effect on firm value.